Effectiveness of Yijinjing on cognitive and motor functions in patients with Parkinson’s disease: study protocol for a randomized controlled trial - Luo, Kailiang; Ma, Xinran; Jin, Xueming; Liu, Xinhao; Li, Yujia; Ma, Shujie; Hu, Jun (Frontiers in Neurology, 2024)
Background: Parkinson's disease (PD) is a common neurodegenerative disorder that affects motor and non-motor functions, significantly reducing patients' quality of life. No effective drug-based treatments are known to solve this problem. Non-drug therapies such as Yijinjing exercise have shown potential in improving cognitive and motor functions in PD patients. However, solid evidence must still be provided to support their clinical efficacy. This study aims to evaluate the clinical efficacy of Yijinjing exercise interventions in PD patients and explore the underlying mechanisms between the cognitive and motor functions in PD.Methods: This is a single-center randomized controlled trial in which 96 eligible PD patients will be randomly assigned to receive either Yijinjing exercise group or brisk walking group or control group in a ratio of 1:1:1. Interventions (Yijinjing exercise or brisk walking training, 40 min per session) will be provided in 3 sessions per week (Monday, Wednesday, Friday) for 12 weeks, with a total of 36 sessions.After the treatment, there will be a 1-month follow-up period. The primary outcomes will be measured using the Montreal Cognitive Assessment (MoCA) and the Unified Parkinson's Disease Rating Scale motor section (UPDRS-Ⅲ). Secondary outcomes include balance function, executive function, walking function, sleep quality, and quality of life. Additionally, the prefrontal cerebral and sensorimotor cortex blood oxygen signal level will be collected to explore the underlying mechanisms. All outcomes will be assessed at baseline, at the end of 12 weeks of treatment and after an additional 1-month follow-up period.The results of the study protocol will provide high-quality evidence for the potential of intervention measures based on the Yijinjing exercise to improve the cognitive and activity levels of Parkinson's disease patients. We envision the Yijinjing exercise as a non pharmacological family activity that can provide a new and more effective method for the treatment of Parkinson's disease patients or those at risk. Trial registration: This study was approved by the Ethics Committee of the Second Rehabilitation Hospital of Shanghai (2020-05-01). The trial has been registered in the China Clinical Trials Registry (ChiCTR2200055636).